165k views
4 votes
3x + 4x +7y +5z = 4x + 55y

Simplify the equation.

User Jbww
by
5.9k points

2 Answers

4 votes

Answer:

3x - 48y + 5z = 0

Explanation:

First simplify the sides.

7x + 7y + 5z = 4x + 55y

Subtract the like terms:

3x - 48y + 5z = 0

User Gaspar Teixeira
by
5.8k points
4 votes

Answer:

3x - 48y +5z = 0

Explanation:

3x + 4x +7y +5z = 4x + 55y

Combine like terms

7x+7y+5z = 4x+55y

Subtract 4x from each side

7x -4x+7y+5z = 4x-4x+55y

3x +7y +5z = 55y

Subtract 55y from each side

3x +7y - 55y +5x =0

3x - 48y +5z = 0

User Jason Hartley
by
5.6k points